Influence of BaFe12O19 on structure, sintering and bioactivity behavior in bioactive glass - Intawin P. (American Scientific Publishers, 2015)
Copyright © 2015 American Scientific Publishers All rights reserved. The aim of this work was to study the physical, mechanical and bioactivity properties of bioactive glass based composites containing BaFe12O19 (BF) by using the modified solid-state sintering method. The structure and microstructure of the samples were characterized by differential thermal analysis (DTA), X-ray diffraction, energy dispersive X-ray analysis (EDXA) and scanning electron microscopy. In vitro bioactivity was investigated in simulated body fluid (SBF) for 7 days. The results showed that the glass transition temperature (Tg) and crystallization temperature (Tc) increase when the level of BF increases from 5 to 20 wt.%. Na6Ca3Si6O18 and BaFe12O19 phases were crystallized in all samples. It can be also observed that amount of Na4Ca4Si6O18 phase decreased while that of BaFe12O19 increased with increasing BF content. It was found that BF addition caused an alteration in mechanical behavior. In addition, the apatite was formed on the surface layers of the glass-ceramics confirming Delivered their biocompatibility.